Mid-Term Outcomes of Minimally Invasive Direct Coronary Artery Bypass Grafting - Reser, Diana; Hemelrijck, Mathias van; Pavicevic, Jovana; Tolboom, Herman; Holubec, Tomas; Falk, Volkmar; Jacobs, Stephan (The Thoracic and Cardiovascular Surgeon, 2015)
Background Minimally invasive direct coronary artery bypass grafting (MIDCAB) has gained wide acceptance for the treatment of single vessel disease of the left anterior descending artery (LAD). Here, we present our single center experience of 152 consecutive patients.Materials and Methods All patients underwent MIDCAB through a left anterior minithoracotomy between January 1, 2009, and December 31, 2012. Preoperative, intraoperative, postoperative, and follow-up data including major adverse cardiac and cerebrovascular events (MACCE) and need for re-intervention were collected.Results Mean age was 64.4 ± 11 years, median additive EuroSCORE 3 (0–11), 84% were male. All except one patient were successfully operated without cardiopulmonary bypass. Seven patients with unexpected severely calcified LADs were converted to sternotomy (4.6%); 91.3% were extubated in the operating room or on the day of surgery. Median stay at the intensive care unit and in hospital were 1 (0–97) and 7 (1–49) days, respectively. Thirty-day mortality was 1.9%. There was no stroke. Five patients (3.2%) had to be re-explored for bleeding and 95% received no transfusion. Median follow-up was 24 months (0–97) and complete in 93.3% with overall survival of 92.4 ± 0.2% and MACCE-free survival of 96.1 ± 1.7%. Two patients had a re-intervention of the LAD.Conclusion MIDCAB is a safe procedure with low postoperative morbidity, mortality, and favorable mid-term MACCE-free survival in selected patients that should be discussed in a heart team setting to evaluate the “ideal” individual treatment option.
Keywords: coronary artery bypass grafts surgery; CABG; cardiac; off-pump surgery